Exploratory case study research: outsourced project failure - Verner, June M.; Abdullah, Lili Marziana (Science Direct, 2012)
Context: IT plays an increasingly strategic role in the business performance of organizations, however, the development of strategic IT systems involves a high degree of risk and outsourcing the development of such systems increases the risk. Objective: Using a case study approach we build on research that identifies risk factors leading to the failure of outsourced strategic IT development projects. We investigate the BSkyB project, a strategic development project, which was the subject of recent litigation in the British High Court. We wish to discover what factors led to the failure of such a high profile project; in particular we wish to identify which factors were under the control of the client. We also review the usefulness of the case study methodology when it is not possible to interview any of the people involved with a project. Method: Detailed-step-by-step guidelines designed for multiple industrial case studies are used to investigate the failure factors of the BSkyB project. We use transcripts of court proceedings and media reports to determine the failure factors. We compare the factors identified with those in a conceptual risk framework developed in prior research thus providing an initial validation of that framework. Results: The following factors were identified as problems in the BSkyB project: contract, requirements, project complexity, planning and control, execution, and team. A time and materials contract was a risk not originally included in the risk framework that we used. Conclusion: The BSkyB project failed because of problems that can be traced to both client and vendor. According to the judge’s summing up the major fault was with the vendor, although some problems did emanate from the client side. We found that many sections in the case study methodology we used were unnecessary for a single case study based on court proceedings and media reports. The risk framework helped with risk identification.